INTEGRATING LOCAL WISDOM OF PIIL PSENGGIRI INTO ENGLISH LANGUAGE TEACHING - Rosmalita Septiana; Divia Khairunita; Haanii Pradini; Fivty Travika Sukma; Restina Damayanti (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
Cultural content has been a crucial issue in English language teaching. Nevertheless, the local cultural content of Lampungnese, called piil psenggiri, has not yet been widely discussed among the scholarly community. This paper, therefore, offers a rich description of the integration of piil psenggiri values into English language instruction in an Islamic boarding school in Lampung province. This research followed a case study of the qualitative method. It involved in-depth interview with English teacher and students of Islamic boarding school. This research study reveals that the participants consider the values of piil psenggiri should be incorporated into the English language teaching in Lampungnese context for two main reasons. First, piil psenggiri belongs to local wisdom that should be preserved through educational practices in Lampung. Second, the integration of piil psenggiri should be properly conducted through some instructional variables such as reading texts, classroom activities, tasks, and the learning environment.